2012
DOI: 10.1073/pnas.1209277109
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of subunit CCT3 in the yeast chaperonin CCT/TRiC with Q/N-rich proteins revealed by high-throughput microscopy analysis

Abstract: The eukaryotic chaperonin containing t-complex polypeptide 1 (CCT/TRiC) is an ATP-fueled machine that assists protein folding. It consists of two back-to-back stacked rings formed by eight different subunits that are arranged in a fixed permutation. The different subunits of CCT are believed to possess unique substrate binding specificities that are still mostly unknown. Here, we used highthroughput microscopy analysis of yeast cells to determine changes in protein levels and localization as a result of a Glu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
5
29
0
Order By: Relevance
“…CCT1 was previously shown to interact and sequester the N17-huntingtin exon 1 fragments101112 as well as polyQ stretches51. Here we confirmed that CCT2 interacted with huntingtin fragments, polyA stretches, mutant ATXN3 and p62.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CCT1 was previously shown to interact and sequester the N17-huntingtin exon 1 fragments101112 as well as polyQ stretches51. Here we confirmed that CCT2 interacted with huntingtin fragments, polyA stretches, mutant ATXN3 and p62.…”
Section: Discussionsupporting
confidence: 85%
“…Our data extend beyond the CCT–HTT interaction10111251, as we have seen similar interactions with other autophagy adaptors/cargos such as ATXN3, p62 or polyA tract that indeed accumulate in a similar autophagy-dependency pattern upon CCT depletion. The effects of the CCT depletion on the aggregation and oligomerization of mutant huntingtin fragment, polyalanine expanded proteins, mutant ATXN3 and p62 are primarily autophagy dependent, as opposed to the current assumption that these proteins are direct clients of physiological CCT activity and that this direct chaperone activity on mutant huntingtin is entirely responsible for its anti-aggregation properties (Figs 5 and 6).…”
Section: Discussionsupporting
confidence: 75%
“…Its mammalian and yeast counterparts were originally found to be involved in the correct folding of actin and tubulin, 9 while more recent studies have shown that it actually has a broader range of substrate binding and folding capacity. 10 The potential binding between T-complex and PEX7 is also supported by a previous report in a mammalian system showing that T-complex interacts with the WD40 domain, 11 which largely constitutes PEX7 within the peptides. 12 Because PEX5 also interacts with the WD40 domain of PEX7 for subsequent cargo import, 13 it is tempting to hypothesize that T-complex and PEX5 may competitively bind to PEX7 in the cytosol, in which case T-complex may function as a negative regulator for the import of PTS2-containing proteins.…”
supporting
confidence: 50%
“…Protein folding is mediated in the eukaryotic cytosol by the TCP-1 ring large multi-subunit complex (TRiC), also called CCT [1][2][3][4][5]. The TCP/ TRiC/CCT1 chaperonin is a highly conserved, macromolecular enzyme comprised of two hetero-oligomeric stacked rings with eight different subunits each [3][4][5][6][7][8]. Both genetic and biochemical evidence reveals that the TRiC complex is required for folding of many essential proteins, including the cytoskeletal proteins myosin, actin and tubulin [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%